Subacute sclerosing panencephalitis. Issue 635 (September 1978) - Bellman, M. H.; Dick, G.
Abstract : Subacute sclerosing panencephalitis (SSPE) is now considered to be caused by measles virus. There are four diagnostic criteria, namely the clinical picture, a characteristic EEG, serology of serum and CSF and brain histology. A register of cases in the U.K. has been kept since 1971, and up to September 1977, ninety-six patients have been reported. The male/female ratio is 2 : 1. The disease most commonly affects children between the ages of nine and eleven years who usually have had measles at a very early age. The average delay between the measles infection and onset of SSPE was 6.8 years and of the thirty-four patients known to have died the average survival times was 1.2 years. There are still many questions about the pathogenesis and epidemiology of SSPE that have yet to be answered.